Soil Conditioner Formula Enriched by Humic Substance to Enhance Productivity of Ultisols Taman Bogo, Lampung - AI DARIAH; N.L. NURIDA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
The objectives of this research are : (1) to find enrichment substance from various organic material to increase the effectiveness of the soil conditioner, (2) to study the effect of humic substance contained in organic matter on soil properties and crop productivity. Research preceded by humic substance extraction from various organic matter. Reseach was conducted at green house using Ultisols from Taman Bogo, Center of Lampung. The experimental design used a factorial with four replications, treatment that tested were factor I: some organic material: municipal waste compost, manure compost, coal and peat, whereas factor II: enrichment types: extracted (HLS) and no extracted. The results of the research showed that HLS (humic like substances) from peat contained the highest humic substances (humat and fulvic acid), whereas HLS from manure contained the lowest humic substance. Manure was better applied in the form of compost than HLS. Organic materials with a high C/N ratio and low nutrient content (i.e. coal, peat, municipal wastes), that was applied in HSL form did not effect plant growth and biomass production significantly.